The Relationship Between Adolescent Women's Behavior Towards the Effects of Use of Natural Pain Relief in SMP Negeri 1 Panci Tongah, Simalungun Regency - Hendri Kurniawan; Ismi Noer Fadilah; Putri Permata Sari; Nur Love Suci Fairu (International Journal of Public Health Excellence (IJPHE), 2022)
Menstruation (menstruation) is the periodic discharge of blood and body cells from the vagina that originate from the lining of a woman's uterus. Menstruation begins at puberty and marks a woman's ability to bear children, although other health factors may limit this capacity. This event is so natural and natural that it is certain that all normal women will experience this process. However, in reality many women experience menstrual problems, one of which is menstrual pain (dysmenorrhea) (Admin, 2008). The research was conducted at Panei Tongah Public Middle School 1, Simalungun Regency, on 139 respondents. There is a relationship between knowledge and the effect of using menstrual pain relievers at SMP Negeri 1 Panci Tongah, Simalungun Regency, with the P-Value of 0.001 0.05. There is no relationship between attitudes towards the effect of using menstrual pain relievers at Panei Tongah 1 Public Middle School, Simalungun Regency, where the value obtained is greater than the expected value (P Value 0.250 0.05). There is a relationship between action and the effect of using menstrual pain relievers at Panei Tongah 1 Public Middle School, Simalungun Regency. From the results of the Chi-square test, the P-Value is 0.001 0.05, so the hypothesis is accepted. It is hoped that young women will pay more attention to the effects of excessive use of pain relievers because this can be bad for health. It is hoped that the school will work closely with health workers to conduct health education in schools, especially for young girls.